A new species of Megalachne (Poaceae) endemic to Alejandro Selkirk Island, Juan Fernandez Archipelago, Chile - Penneckamp Furniel, Diego; Rojas Villegas, Gloria (Phytotaxa, 2019)
A new species of Megalachne (Poaceae) endemic to Alejandro Selkirk Island, Juan Fernandez Archipelago, Chile, is described and illustrated, based on morphological characters. This species is differentiated from others of the genus by its long lemma awn (5–8.5 cm) and by the number of flowers in the spikelet (2–4). The taxon has been reported previously for Juan Fernandez endemic flora, but without formal description.